Extractive Text Summarization Using Neural Network - Nadeen M ABDELALEEM; Hatem M ABDAL KADER; Rashed K SALEM; Diaa SALAMA ABD ELMINAAM (Communications of International Proceedings, 2020)
Lately, with the availability of huge amounts of data over the internet,  it becomes difficult and necessary need to get information vastly and accurately in order to extract the related information . we need a good mechanism automatic text summarization becomes a useful technique for generating the summary from single or multiple documents related to the users query the operation of text summarization is condensing the original text into a shorter form this paper focus on extractive text summarization for summarizing text using neural networks which is trained on a set of features extracted from sentences that should be included in the summary of the text.
Keywords: Automatic text summarization – extractive text summarization- Features-neural network.